NILAI-NILAI PENDIDIKAN ADAB MENUNTUT ILMU DALAM KITAB AL-ILMU SHAHIH BUKHORI KARYA IMAM AL-BUKHORI - Lubis, M. Fauzi; Arrosyidi, Hofwan (Jurnal Sabilarrasyad, 2021)
The purpose of this study is to: 1) Find out about Imam Bukhori; 2) Knowing the position of the book of Al-Ilmu Shahih Bukhori by Imam Al-Bukhori in islamic studies; 3) Knowing the values of education is demanding knowledge in the book of Al-Ilmu Shahih Bukhori by Imam Al-Bukhori. This research method uses Library studies. The results showed that the journey of Imam Bukhari's life in demanding knowledge with an extraordinarily great memory possessed from childhood that made many people amazed and did not expect that greatness can be owned let alone he never showed or showed off his greatness to brag. Meanwhile, Imam Bukhari has also experienced the sadness of living as an orphan and has also experienced tremendous pain in his eyes to experience blindness and with Allah's permission his vision is healed again. The intelligence and greatness of Imam Bukhari with his memory does not always go well because in life.